2023
DOI: 10.1177/13623613231213283
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing mechanisms of caregiver-mediated naturalistic developmental behavioral interventions for autistic toddlers: A randomized clinical trial

Maranda K Jones,
Bailey J Sone,
Jeffrey Grauzer
et al.

Abstract: To address the variability of naturalistic developmental behavioral intervention outcomes, the current study sought to isolate the effects of the instructional strategies of caregiver-mediated naturalistic developmental behavioral interventions. In this comparative efficacy trial, mothers of 111 autistic children (18–48 months) were randomized to learn one of two sets of naturalistic developmental behavioral intervention language facilitation strategies (responsive or directive). We aimed to characterize the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Marama's desire for the programme to take '…another step up' may have been met had the support lasted longer and more directive teaching strategies were used. Recent research conducted by M. K. Jones et al (2023) found that directive strategies alone (e.g., providing child communication opportunities followed by prompts) led to significantly greater communication outcomes than responsive strategies only (e.g., following the child's lead and modelling language). Responsive strategies were, however, associated with a greater number and longer length of child supported engagement (i.e., engagement with a mutual focus where the child does not exhibit directed gaze or communication to the adult).…”
Section: Adaptations and Neurodiversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Marama's desire for the programme to take '…another step up' may have been met had the support lasted longer and more directive teaching strategies were used. Recent research conducted by M. K. Jones et al (2023) found that directive strategies alone (e.g., providing child communication opportunities followed by prompts) led to significantly greater communication outcomes than responsive strategies only (e.g., following the child's lead and modelling language). Responsive strategies were, however, associated with a greater number and longer length of child supported engagement (i.e., engagement with a mutual focus where the child does not exhibit directed gaze or communication to the adult).…”
Section: Adaptations and Neurodiversitymentioning
confidence: 99%
“…Responsive strategies were, however, associated with a greater number and longer length of child supported engagement (i.e., engagement with a mutual focus where the child does not exhibit directed gaze or communication to the adult). Although there are some methodological challenges within the study conducted by M. K. Jones et al (2023), for example in the ways in which directive and responsive strategies were divided and defined, it may be that the use of responsive, relationship-based strategies from the ESDM in Study 3 aligned with Marama's goal for increased engagement with Rawiri. However, given it appears as though directive strategies may be useful for increasing communication (M. K. Jones et al, 2023), it is imperative that future research examine ways in which directive strategies may be defined, and the extent to which such strategies align with neurodiversity affirming approaches.…”
Section: Adaptations and Neurodiversitymentioning
confidence: 99%